this might help.
Can anyone give me a 'walk through talk through' of the following problem?
Use the Laplace Transform method to obtain the forced response of the system
assuming zero initial conditions and t>=0 for the following cases:
Fingers crossed someone can help. I've been wrestling with it for a couple of days now.
Thanks. I've done most of these now. I've just hit a sticking point with the last one. I've a feeling I've missed something obvious. I've got to...
1/(s+1)^2(s+2)= A/(s+1) + B/(s+1)^2 + C/(s+2)
1= A(s+1)(s+2) + B(s+2) + C(s+1)^2
Let s = -2 Let s = -1
C = 1 B=1
Is this right and how do I find A?